PSYCHOLOGICAL AND PEDAGOGICAL ASPECTS OF STUDENT EDUCATION IN THE CONDITIONS OF MODERNIZATION OF HIGHER EDUCATION AND APPLICATION OF DISTANCE TECHNOLOGIES - Нovorun Tetiana; Belous , Olena; Berladir Кristina; Khaniukov , Kirill; Varakin , Vitaly (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The article analyzes the psychological and educational patterns of learning and acquisition of skills by students in the two systems of education. The first system is considered - a system of organizing learning in which the teacher is directly involved in almost all stages of formation and learning. Second - credit-modular system, which provides a lot of independent work of students and provides an opportunity to use distance learning technologies. The paper made an analysis of the advantages and disadvantages of these two systems of education in high school. The authors see the efficiency of modern education combined some aspects of these two systems.